2022
DOI: 10.1038/s41467-021-27642-5
|View full text |Cite
|
Sign up to set email alerts
|

Climate changes modulated the history of Arctic iodine during the Last Glacial Cycle

Abstract: Iodine has a significant impact on promoting the formation of new ultrafine aerosol particles and accelerating tropospheric ozone loss, thereby affecting radiative forcing and climate. Therefore, understanding the long-term natural evolution of iodine, and its coupling with climate variability, is key to adequately assess its effect on climate on centennial to millennial timescales. Here, using two Greenland ice cores (NEEM and RECAP), we report the Arctic iodine variability during the last 127,000 years. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 98 publications
(160 reference statements)
1
10
0
Order By: Relevance
“…These correlations/similarities indicate that meltwater discharge into the Labrador Sea/subpolar regions might have caused/contributed to the cooling in the highlatitude North Atlantic during the Allerød period. Surface freshening/sea ice expansion in the subpolar regions and following weakened ocean circulation 59 (i.e., limited subpolar gyre and Atlantic Water inflow) could have restricted oceanatmosphere heat exchange and heat transport northward, resulting in a decline in atmospheric temperatures 50,60 , which may also be applied to the other meltwater events (Fig. 6b).…”
Section: Discussionmentioning
confidence: 99%
“…These correlations/similarities indicate that meltwater discharge into the Labrador Sea/subpolar regions might have caused/contributed to the cooling in the highlatitude North Atlantic during the Allerød period. Surface freshening/sea ice expansion in the subpolar regions and following weakened ocean circulation 59 (i.e., limited subpolar gyre and Atlantic Water inflow) could have restricted oceanatmosphere heat exchange and heat transport northward, resulting in a decline in atmospheric temperatures 50,60 , which may also be applied to the other meltwater events (Fig. 6b).…”
Section: Discussionmentioning
confidence: 99%
“…While precipitation and dry deposition are primary terrestrial iodine sources, the amount of iodine present in the terrestrial atmosphere, referred to as the effective source, directly influences the prevalence of iodine deficiency disorders. The ocean, being the major iodine reservoir on the Earth’s surface, releases a substantial amount of iodine into the atmosphere from its surface, and this oceanic emission is subsequently transported to the terrestrial environment, serving as the primary terrestrial iodine source. Greenland ice core records revealed that bioproductivity-modulated iodine emissions from the ocean’s surface have determined atmospheric iodine concentrations on land throughout the Holocene, and a noticeable increase since 1950 has been found due to anthropogenic impact, particularly in the summer; however, the impact during winter months has been much less pronounced …”
Section: Introductionmentioning
confidence: 99%
“…The ocean, being the major iodine reservoir on the Earth's surface, releases a substantial amount of iodine into the atmosphere from its surface, and this oceanic emission is subsequently transported to the terrestrial environment, serving as the primary terrestrial iodine source. 3−5 Greenland ice core records revealed that bioproductivitymodulated iodine emissions from the ocean's surface have determined atmospheric iodine concentrations on land throughout the Holocene, 6 and a noticeable increase since 1950 has been found due to anthropogenic impact, particularly in the summer; 7 however, the impact during winter months has been much less pronounced. 8 Considering that coal combustion releases considerable amounts of iodine into the air, 9 a heightened iodine concentration is anticipated over the terrestrial atmosphere during the winter season in Chinese megacities, especially in the northern regions where coal usage is elevated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The boundary of geological ages was set as following GSSA (Cohen et al 2015). In our analyses, we defined the Last Glacial Period as a period separate from the Pleistocene, from the end of the Eemian Last Interglacial Period (0.115 Ma) to the end of the Younger Dryas stadial (0.0117 Ma) (Corella et al 2022). Based on the information described in each literature, we applied the finest and most reliable classification age/ interval for individual fossil records.…”
Section: Discussionmentioning
confidence: 99%